(untitled) (Lafia Journal of Scientific and Industrial Research, 2026)
This study offers new insights into naturally occurring radioactive minerals in the Azara area and its environs, focusing on their impact on radiogenic heat production (RHP) for exploration geothermal energy. The radiometric data were analysed in relation to the lithology of the study area to determine the contribution of each lithologic unit to the estimated RHP. The study assessed radioelement concentrations, spatial distributions, and statistical summaries for each lithologic unit. Using radiometric data, the study mapped and analysed the spatial occurrence of potassium (K), thorium (eTh), and uranium (eU). The results show average concentrations of 1.23 % for K, 12.15 ppm for eTh, and 3.38 ppm for eU. Compared with crustal averages, K levels were lower, while eTh and eU levels were slightly higher. Radioelement abundance varied across rock types, with the highest concentrations in shales, siltstones, and sandstones. Estimated RHP values ranged from 0.90 to 2.70 uWm−3, with an average of 1.70 uWm−3. The estimated RHP value falls within the typical crustal range but is below the 4.0 uWm−3 threshold for a viable geothermal energy source.